59 Turning adversity into opportunity: undergraduate led improvisation in teaching methods. (16th November 2020) - Anne, Anvita; Bandi, Varun Kumar; Pusuluri, Satyanarayana Murthy
Abstract : Introduction: There is a need for simple teaching methods every teacher can adopt, which are accepted by the students and provide a sustainable outcome. The traditional teaching methods do not achieve the desired outcomes, with many students left wanting for more practice of procedural skills. Methodology: MBBS Phase I students were randomly distributed into 3 groups: Group 1 (traditional method, n=30), Group 2 (Peyton's method, n=30) and Group 3 (Modified Peyton's method, n=30), and study duration was 6 months. Students were taught anatomy of the neck veins and were taught central venous catheterizations (CVC) into the right internal jugular vein by a single nephrologist on a mannequin. The modified Peyton's method consists of: Demonstration and Deconstruction, Comprehension, Performance and Observation, Teacher and Peer Feedback. The students were followed up with 4-week and 12-week recall. Results: The mean percentages obtained at end of 4 weeks in Groups 1, 2 and 3 were 82±10%, 86.67±7%, and 87.33±6.9% respectively. The percentages obtained at end of 12 weeks were 74.5±7.6%, 80.5±7.5% and 80.3±7.1% respectively. There was a significant decrease in percentages in all the groups (p<0.001). At 4 weeks, there was significant difference between Groups 1 and 2, Groups 1 and 3 (p<0.05), while difference between Group 2 and 3 was not significant. At 12 weeks, there was significant difference between Groups 1 and 2 (p<0.01), Groups 2 and 3 (p<0.01) while there was no significant difference between Groups 2 and 3. The number of students confident of performing the procedure in Groups 1, 2 and 3 were 30%, 56.7% and 60% respectively. There was significant difference in the confidence level between Group 1 and 2 (p<0.05), Group 1 and 3 (p<0.05), while the difference was non-significant between Group 2 and 3 (p=0.793). Conclusion: This study highlights the effort of a student in turning her adversity into an opportunity to improve the educational methods.